Magnitude and factors associated with anxiety and depression among patients with breast cancer in central Ethiopia: A cross-sectional study - Belay, Winini; Labisso, Wajana Lako; Tigeneh, Wondemagegnehu; Kaba, Mirgissa; Haileselassie, Werissaw (Frontiers in Psychiatry, 2022)
Background Patients with breast cancer are assumed to be susceptible to anxiety and depression, while there is a lack of evidence about the epidemiology and underlying factors in Ethiopia. Hence, we aimed to assess the prevalence and predictors of anxiety and depression among patients with breast cancer in Ethiopia. Method An institutional-based cross-sectional study was conducted among patients with breast cancer who were attending treatment at the Oncology Center of the Tikur Anbessa Specialized Hospital, the largest referral teaching hospital in Ethiopia. The Hospital Anxiety and Depression Scale (HDAS) was used to evaluate the anxiety and depression status of the participants, and a structured questionnaire was used to collect sociodemographic, socioeconomic, and clinical data from the participants. Medical records of the participants were reviewed to collect and correlate information about the grade and stage of cancer. An analysis was done using STATA 15.1. Results The study included 333 randomly selected participants, of which 35.4% were on stage III and 33% on stage II, and 67.9% were on chemotherapy and surgery. The prevalence of anxiety and depression were 60.7 and 58.6%, respectively. Poor patient-provider interaction (adjusted odds ratio [AOR] = 4.5, 95% CI: 2.49, 8.12) and having no financial support (AOR = 2.83, 95% CI: 1.63, 4.91) were the significant predictors of anxiety. Age >49 years (AOR = 0.48, 95% CI: 0.25, 0.90), poor patient-provider interactions (AOR = 3.36, 95% CI: 1.87, 6.02), and having no financial support (AOR = 3.36, 95% CI: 1.95, 5.79) were the significant predictors of depression. Conclusion In this study, the prevalence of anxiety and depression was high among patients with breast cancer, and the lack of financial support and poor patient-provider interactions were significant predictors of anxiety and depression among these groups of patients. Patients with cancer need regular screening for mental health and better emotional support from their healthcare providers and families to prevent and treat anxiety and depression.